Effectively enforcing mandatory vaccination in Poland and worldwide - Paplicki, Mateusz; Susło, Robert; Benedikt, Antoni; Drobnik, Jarosław (Family Medicine & Primary Care Review, 2020)
Vaccinations are a crucial preventative measure performed by primary care. Polish local self-governments should be praised for their independent determination in attempting to improve public health by requiring parents to fulfill their legal obligation to have their children receive mandatory vaccinations. However, there is an urgent need for similar general regulations encompassing the entire population of Poland if serious risks to its public health are to be avoided. The variety of approaches attempted thus far in different countries demonstrates that there is no single ideal solution for all – although, judging by the results, it seems that incentive-based solutions seem to be more efficient than the repressive ones. We thus advised that Poland implement an escalating approach: proper education of all citizens in human biology and the basics of medicine is a must, as is demonstrated by the experience of Scandinavia; this should begin even in preschool facilities. The “No Jab No Pay” approach used in Australia could easily be replicated in Poland by withdrawing the right to the relatively new child benefit from parents who do not have their children vaccinations ¬– especially as this benefit is ultimately planned to include all children in the country. Following the examples of the Czech Republic, France, Italy, and the United States, unvaccinated children could be banned from entering sports facilities. In case of the most persistent violators, harsh measures – including financial penalties imposed by the state – should be kept in reserve, and these should be similar to the significant fines known from Italy and Germany.